Analysis of Student’s Conceptual Understanding on Visualization Phase in Learning Geometry by Using Spinning Wheel Media - Riny Sulfiyah; Baiduri Baiduri; Agung Deddiliawan Ismail (Department of Mathematics Education University of Muhammadiyah Malang, 2019)
This research aimed to describe the result of using the spinning wheel with steps based on Van Hiele theory, and to know student’s conceptual understanding in visualization phase through spinning wheel media and to describe the effectiveness of spinning wheel in improving student level of thinking from visualization phase to analysis phase. This research was descriptive research on experimental teaching which the research subject was seventh grade students at junior high school 4 Pamekasan consisted of 26 visualization phase students. The data collection techniques used in this research were observation, test, and interview. The resulting research showed that the learning process by using Van Hiele learning theory and spinning wheel media could attract student’s interest in the learning process, so students had the good conceptual understanding. Besides, the result showed the student’s understanding level at SMP 4 Pamekasan, it divided into two categories which were very good; and good. In the very good category, the average score was 89,5%. Then, a student’s conceptual understanding in the good category has 70,99% as the average score. It also stated that the spinning wheel that had been used was effective. It stated as effective because the spinning wheel media could improve from student’s visualization thinking to student’s analytical thinking level.